Temporal patterns of alterations in obesity index, lipid profile, renal function and blood pressure during the development of hypertension in male, but not female, rats fed a moderately high-fat diet. (4th July 2022) - Nazari, Somayeh; Moosavi, Seyed Mostafa Shid
Abstract: Context: Male Sprague-Dawley rats consuming a moderately high-fat (MHF)-diet diverge into obesity-prone (OP) with hypertension and obesity-resistant. Objectives: To study the temporal inter-relationships between body-weight, obesity-index, plasma lipid-profile, renal functional parameters and systolic-pressure alterations during 10-weeks feeding MHF or normal diet to male and female rats. Methods: Body-weight, obesity-index and systolic-pressure were measured weekly, while metabolic-cage and blood-sampling protocols were performed every other week. After 10-weeks, renal excretory responses to acute salt-loading and renal autoregulation were examined. Results: The male-OP group had progressively increased body-weight, plasma-triglyceride and systolic-pressure from Weeks 2, 4 and 5, respectively, lower renal sodium-excretion at weeks 4–8 and finally, delayed excretory response to salt-loading and rightward and downward shifts in renal autoregulatory curves compared to all other groups. Conclusion: Feeding the MHF-diet in male-OP rats led to a greater weight-gain and adiposity followed by the development of atherogenic-hyperlipidaemia and persistently impaired pressure-natriuresis to induce hypertension.